Fontes e doses de giberelina no desempenho de arroz anão em biotestes - Martins, Raphael Gonçalves; De Camargo E Castro, Paulo Roberto; Araujo, Diego Kitahara; Silva, João Marcelo [UNESP]; Martins, Maria Bernadete Gonçalves [UNESP] (My University, 2012)
Mutant of dwarf rice (Oryza sativa L.) were treated with three different concentrations of gibberellic acid originated from two sources (Gibberellin and Pro-Gibb) and submitted to the determination of bigger height, in relation to the soil leveI. Mensurations were realized in each seven days at greenhouse conditions under mean temperature of 25°C. lt was concluded that concentrations of 10 mg L-1 of gibberellin originated from Pro-Gibb or Gibberellin was enough to promote a differentiated performance of the test plant. For the study of leaf anatomy Pro-Gibb presented, under all tested concentration, increase of mesophyll thickness in relation to Gibberellin. In this analysis, source and interaction between source and concentration applied promoted significant variations between the mean data.
Gibberellin sources and doses on development of dwarf rice in biotests
Keywords: Biological test; Dwarf revertion; Gibberellic acid